Nature-Based Interventions Promoting the Well-Being of Finnish Youth Outside Education or Employment - Obeng, James Kutu; Kangas, Katja; Manninen, Outi; Stamm, Ingo; Tolvanen, Anne (Taylor & Francis, 2025)
Nature-based interventions have a potential to activate and rehabilitate youth facing challenges with social, mental, or physical functioning. In Finland, nature-based interventions have been integrated into youth workshops to foster sustainable well-being. Using an exploratory mixed-methods design, this study explores the value of nature-based interventions for the well-being of Finnish youth outside education or employment. Participants (N = 18, aged 20-26) were drawn from three nature-based youth workshops. Sixteen participants completed survey questionnaires assessing the cognitive and social outcomes of the interventions and the key elements contributing to their effectiveness. Nine participants took part in qualitative interviews. Thematic analysis of the interview data revealed that the interventions promoted factors supporting well-being, including physical activity, structure and routine, skill development, social belonging, and meaningful participation. Participants also reported enhanced connections with nature and sustainable lifestyles. Central to these well-being experiences were the therapeutic benefits of nature, meaningful nature-related activities, and supportive social contexts. This study provides valuable insights for social workers and social service professionals to leverage nature for health and social outcomes among marginalized youth. Future research should investigate young people’s preferred environments and activities toward developing tailored nature-based interventions that promote positive well-being experiences.
Keywords: nature-based interventions; well-being; youth; social work; Finland